Fotodegradação de efluente de terminal de combustível com catalisadores dopados - Ferrari-Lima, Ana Maria (2013)
Wastewater derived from petrol products has high organic load and high toxicity, mainly due to the presence of a large number of aromatic hydrocarbons, such as BTEX (benzene, toluene, ethylbenzene and xylene). The toxicity of petrol stations wastewater remains high even after water-oil separation tanks. Given the need for further treatment of these effluents, this work evaluated the efficiency of heterogeneous photocatalysis in the removal of these toxic compounds. Doped and undoped mixed catalysts were synthesized from TiO2, ZnO, and Nb2O5 by sol-gel method. The atomic load of doped nitrogen was found to be approximately 0.5 at%. Photocatalytic tests were performed with radiation from a 46W blacklight lamp (UVA radiation) and a 16W white LED lamp (visible radiation). Assays were carried out with synthetic wastewater containing 100 ppm of benzene, toluene and xylene and with the wastewater collected in a petrol station located in Maringá-PR. The reaction efficiency for the synthetic solution degradation was monitored by gas chromatography applying the headspace technique. The reaction efficiency for the collected wastewater was monitored by turbidity, COD, TOC and acute toxicity removals. The reactions followed the first-order kinetics and the best results were obtained with the N-doped TiO2/ZnO catalyst, which showed kinetics constants of 24x10-3 min-1 and 8.64x10-3 min-1 for BTX removal under UVA and visible radiations, respectively. Regarding to the real wastewater, kinetics constant of 2.4x10-3 min-1 was found for COD removal under visible radiation and the elimination of toxicity was achieved with the same catalyst.